2016
DOI: 10.1007/978-3-319-33111-9_5
|View full text |Cite
|
Sign up to set email alerts
|

Publish and Subscribe Pattern for Designing Demand Driven Supply Networks

Abstract: Logistic flows, business process management and collaboration remain a major problem in the supply chain. In this article we are going through this issue to propose an integrative and collaborative approach. More precisely, we develop a cloud-based and service-oriented bus for business interoperability for logistic flows. Though the bus, we define protocols and standards allowing the integration of data formats which are for the most proprietary and heterogeneous. The bus also allows data sharing between proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Ferreira et al (2012) mentioned that the concern over data confidentiality creates corporate resistance to engage in whole-chain collaboration more actively as some members interacting within the network may be each other's competitors on other services. Gnimpieba Zanfack et al (2015) stated that the next question asked by companies, after the issues of data interoperability, is how supply chain partners will share data with all their partners, considering the confidentiality, security, access right, and service level agreement (SLA) of the shared data. If not properly governed, data-sharing can lead to the loss of protection over their formulation information and adverse effects on their competitive advantages.…”
Section: Data Sharing Vs Data Confidentiality and Data Sovereigntymentioning
confidence: 99%
See 2 more Smart Citations
“…Ferreira et al (2012) mentioned that the concern over data confidentiality creates corporate resistance to engage in whole-chain collaboration more actively as some members interacting within the network may be each other's competitors on other services. Gnimpieba Zanfack et al (2015) stated that the next question asked by companies, after the issues of data interoperability, is how supply chain partners will share data with all their partners, considering the confidentiality, security, access right, and service level agreement (SLA) of the shared data. If not properly governed, data-sharing can lead to the loss of protection over their formulation information and adverse effects on their competitive advantages.…”
Section: Data Sharing Vs Data Confidentiality and Data Sovereigntymentioning
confidence: 99%
“…Ferreira et al (2012) and Främling et al (2013) suggested the involvement of software and data integrator companies as the intermediary hub and mapping knowledge base to alleviate such a burden (e.g., by offering a standard compliant ready product, or, a platform that provides message routing and mapping capabilities). For this purpose, Gnimpieba Zanfack et al (2015) and Hofman (2016) suggested the adoption of an ESB that provides protocol adapters for transforming the protocol (or format) of a message sent by a client to another one. supports this by suggesting partnerships with commercial Integration Service Providers (ISPs) as intermediaries to hide the complexities imposed by the adoption of the amplitude of standards, especially for SMEs due to their business demands.…”
Section: State-of-the-artmentioning
confidence: 99%
See 1 more Smart Citation